SCIENTIFIC AND INNOVATIVE DEVELOPMENT OF TURKIC STATES IN THE DIGITAL WORLD - Boyto'rayev Sirojiddin Usmon o'g'li (Modern American Journals, 2025)
This article examines the impact of digital transformation processes on the scientific and innovative development of Turkic states. Modern digital technologies are analyzed as a key factor in advancing science, education, and innovative ecosystems. The study explores opportunities for collaboration among Turkic states, regional specifics of digitalization, and integration with global digital trends. The article offers practical recommendations for promoting scientific research and innovative strategies in the digital world, while evaluating prospects in these fields. The research findings contribute to identifying pathways for the progress of Turkic states in the digital era.
Keywords: Digital transformation, Turkic states, Scientific development, Innovation, Digital world, Technological progress, Educational innovation, Digitalization, Science and technology, Innovative strategies.